INFLUENCE ON EFFICIENCY OF BANKING STOCK RETURN IN INDONESIA STOCK EXCHANGE (IDX) - One, Lasminiasih; Sularto SE, MMSi, Dr. Lana (Accounting, 2009)
In a banking company Financial Statements are a very important thing. Moreover, the company is a very big company and it did go public in the Capital Market Exchange, the Financial Report is very important. Due to the financial statements of a company can know the condition of the company in operation. In addition, Financial reports are also used as a means of making a firm decision on the future, so the company can anticipate events to come. To anticipate this, the banking company should be able to take an efficient action in analyzing something that will happen in the future. This research was aimed to determine the effect of the Efficiency of Bank of Operating Costs: Operating Income (BOPO), Cost Efficiency Ratio (CER), Overhead Efficiency, Opportunity of Capital with Systematic Risk, Price Earning Ratio (PER) with the return of banking companies. The number of sample companies in this research is diguanakan Shebaniah 30 banks listed on the Indonesia Stock Exchange, with the observation period in 2008. Based on the data analysis obtained a significant difference between the efficiency with which the Bank Return can be proved by the results of F